2005
DOI: 10.1007/s11916-005-0021-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of tension-type headache

Abstract: Tension-type headache is one of the most common primary headache disorders. Advances in basic pain and clinical research have improved our understanding of pathophysiologic mechanisms of tension-type headache. Increased excitability of the central nervous system generated by repetitive and sustained pericranial myofascial input may be responsible for the transformation of episodic tension-type headache into the chronic form. Studies of nitric oxide (NO) mechanisms suggest that NO may play a key role in the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 79 publications
(90 reference statements)
3
59
0
7
Order By: Relevance
“…On the other hand other studies have not shown the association of HA in PWM when it is controlled with the presence of depression measured with the Beck Depression Inventory, as Boz et al pointed out [26]. Although Boz et al [26] did not find an association between the HA and migraine, this dimension was associated with tension-type headache, indirectly supporting serotonin involvement in this type of headache, as other authors have described extensively [27].…”
Section: Introductionmentioning
confidence: 93%
“…On the other hand other studies have not shown the association of HA in PWM when it is controlled with the presence of depression measured with the Beck Depression Inventory, as Boz et al pointed out [26]. Although Boz et al [26] did not find an association between the HA and migraine, this dimension was associated with tension-type headache, indirectly supporting serotonin involvement in this type of headache, as other authors have described extensively [27].…”
Section: Introductionmentioning
confidence: 93%
“…It includes tooth clenching, bruxism, tongue thrust, nail or lip biting, sustained contraction of the craniofacial and cervical muscles, and so on. Muscle disorder may increase muscle tenderness at palpation and may be of importance in TTH [23][24][25][26][27][28], and, to some extent, in migraine [29][30][31]. Moreover, muscle disorder can lead to spontaneous myogenous pain in the craniofacial-cervical area [32,33].…”
mentioning
confidence: 99%
“…It is possible that at the very beginning all tension-type headaches begin this way but when there is increased excitability of the central nervous system generated by repetitive and sustained pericranial myofascial input [19] permanency occurs and upregulation creates a cycle of chronic tension-type headache, with lower stimuli requirements needed to trigger the next pain crisis. At the molecular level, chronic tension-type headache has been associated with low serotonin levels [20] acting as an upregulator in the case of migraine, on the other hand, there is the recent description of nitric oxide playing a role in both migraine and tension-type headaches, acting as a cranial and extracranial blood vessel dilator as well as a central nervous system sensitizer, these findings have led to a hypothesis about a common pain pathway shared by all primary chronic cephalalgias or at least between the two major groups, migraine and chronic tension-type headache [21].…”
Section: Physiopathology Of Tension-type Headachesmentioning
confidence: 99%